USA-CHINA ECONOMIC AND STRATEGIC COMPETITION IN THE MIDDLE EAST - Muhammad Owais; Ashfaq Ahmed; Sadaf Ghayoor; Saima Kausar (PalArch's Journal of Archaeology of Egypt / Egyptology, 2022)
United States of America (USA) and China, in the recent times are at loggerheads with each other. From trade war to increasing their spheres of influence, USA and China are getting entangled in different regions of the world Middle East is one of those crucial areas. Middle East has attracted attention and triggered rivalries among many world powers throughout the history. It is primarily because of the massive natural resources trading routes and sea lanes of communications. In pursuit to establish a global world order any major power, would need to consolidate its power in Middle Eastern region. This paper aims to explain strategic and economic interests to understand dynamics of USA-China rivalry in Middle East. Paper underlines Chinese application of neo-liberal approach for the Middle East. It highlights potential for Sino-US Cold War.